Constraints on and facilitators of young people’s participation: The case of border regions of mainland Portugal - Sofia Marques da Silva; Nicolas Martins da Silvaa; Sara Arezes; Paulo Sérgio Martins; Sara Faria; Vitor Dias; Ana Milheiro Silva (Journal of Social Science Education, 2023)
Highlights: